Carbon Dioxide Reduction Options in Power Generation - PRATAP RAGHUVANSHI, SHIV; SINGH, RENU; RAGHAV, A.K.; CHANDRA, A. (Asian Journal of Chemistry, 2010)
Various renewable energy resources like solar, wind, hydro, biomass and geothermal are a suitable option for mitigation of climate change and reducing the carbon dioxide in the atmosphere and have been studied in detail. Advance technologies for CO2 reduction are carbon sinks and sequestration methodologies which involves capture of carbon dioxide from the source, its utilization and disposing of into sinks as stored for long term durations.